MACROECONOMICS FACTOR: THE IMPACT ON STOCK PRICE INDEX - Depari, Genesis Sembiring (Klabat Accounting Review, 2022)
The objective of this study is to determine the link between macroeconomic variables and JCI, STI, and KLSE which are the stock price indexes of Indonesia, Singapore, and Malaysia stock price indexes. Multiple linear regression is used to investigate the influence of four macroeconomic factors on the stock market composite index, namely GDP growth, broad money (money supply), inflation, and interest rate spread. The finding indicates that inflation has a negative effect, while interest rate spread positively affecting the stock price Indexes. Investors may profit from this situation by purchasing blue chips when inflation and interest rates are rising. Keywords: GDP growth, inflation, interest rate spread, money supply, stock price indexes